2013
DOI: 10.5630/jans.33.2_12
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Experienced by Mothers of Children with Pervasive Developmental Disorders and Their Psychological Support

Abstract: Purpose is study aimed to clarify the di culties experienced by mothers of children with pervasive developmental disorders PDD , their psychological support needs and the support apparatus available to them. Methods Ten mothers raising a child with PDD responded to semi-structured interviews. Interview data were analyzed qualitatively. Results e results of the analysis were as follows: 1 Five categories of di culties were identied: Burden due to a lack of adequate medical services and special education at home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, they begin to <worry about entering school>, the issues regarding school attendance that they will face, such as "whether to put them in a special needs class or a regular class", the extent of support they can receive, and whether their children will receive Open Journal of Nursing such support. Anxiety surrounding not knowing how children are doing, given their speech delay and poor expressiveness (d), leads to worry and stress regarding school life in mothers of children with pervasive developmental disorders [25].…”
Section: Preoccupation With Parenting Children With Asd and Their Sib...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they begin to <worry about entering school>, the issues regarding school attendance that they will face, such as "whether to put them in a special needs class or a regular class", the extent of support they can receive, and whether their children will receive Open Journal of Nursing such support. Anxiety surrounding not knowing how children are doing, given their speech delay and poor expressiveness (d), leads to worry and stress regarding school life in mothers of children with pervasive developmental disorders [25].…”
Section: Preoccupation With Parenting Children With Asd and Their Sib...mentioning
confidence: 99%
“…disorders desired support that focused on children's strengths and growth. Attending support facilities supports children's growth and facilitates the mothers' psychological stability by providing venues for consultation [25]. The Act on Support for Persons with Developmental Disabilities came into effect 17 years ago.…”
Section: Using Social Resourcesmentioning
confidence: 99%
“…Moreover, these mothers are unaware of effective approaches to help their children. 14 The difficulties children face during early childhood may differ from those encountered when they reach school age or adolescence; therefore, it is important to provide support to parents according to the age of their children. As mentioned above, previous studies have reported the importance of support to reduce parents' stress and anxiety and the need for parental support for their children's problems depending on the duration before achieving a confirmed diagnosis.…”
mentioning
confidence: 99%